2016
DOI: 10.1088/1367-2630/aa4f63
|View full text |Cite
|
Sign up to set email alerts
|

Thermal shift of the resonance between an electron gas and quantum dots: what is the origin?

Abstract: The operation of quantum dots (QDs) at highest possible temperatures is desirable for many applications. Capacitance-voltage spectroscopy (C(V )-spectroscopy) measurements are an established instrument to analyse the electronic structure and energy levels of self-assembled QDs. We perform C(V ) in the dark and C(V ) under the influence of non-resonant illumination, probing exciton states up to + X 4 on InAs QDs embedded in a GaAs matrix for temperatures ranging from 2.5 to 120 K. While a small shift in the cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…In particular, it explains the occurrence of electronic and excitonic peaks in the C(V) spectrum as well as their respective height. Furthermore, it captures the thermal shift of peak positions connected to the degeneracy of states [17]. In addition, our model also describes and refines the frequency-dependent suppression of peaks which has been reported, e.g., in the work of Luyken [15].…”
Section: Theorysupporting
confidence: 60%
See 4 more Smart Citations
“…In particular, it explains the occurrence of electronic and excitonic peaks in the C(V) spectrum as well as their respective height. Furthermore, it captures the thermal shift of peak positions connected to the degeneracy of states [17]. In addition, our model also describes and refines the frequency-dependent suppression of peaks which has been reported, e.g., in the work of Luyken [15].…”
Section: Theorysupporting
confidence: 60%
“…We identify these arXiv:1710.07545v2 [cond-mat.mes-hall] 14 Dec 2017 peaks with electrons tunneling into nonequilibrium s-, p-, and d-states which are usually inaccessible via the slow DC-sweep in our C(V) spectroscopy. While the simple model of Brinks et al [17] describes the observed quasiequilibrium C(V)-measurement features, we expand this to an extended theoretical model including electron elimination by holes, offering an excellent quantitative agreement with the observed features in the measurements.…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations